The Linguistic Perspectives on Computer Mediated Communication - Chong, Larry Dwan (Beyond Words, 2020)
This paper aims to explore the role of production and perception constraints in computer mediated communication. I review Lindblom's (1990) theory of phonetic variation and propose a new model of linguistic production in Computer Mediated Communication. Cyber citizens use cyber communication as conceptually oral, medially written. The reason to use chat-mode is that it saves time and space (the principle of least effort); here sound, not spelling, is the first thing to be considered. With respect to production in the proposed model, effort is no longer equated with articulatory movement, but rather with the number of keystrokes involved in typing an utterance. On discussing online, discussants show paralinguistic actions such as smile, frown, screaming, etc., and they also reduplicate writings, capitalize all the sentences, and use emoticons; net-communication is headed toward less grammatical and more telegraphic type. The production of hyper-and hypo-forms such as reduplication, punctuation and capitalization will vary according to the sender's estimation of signal-complementary processes and his attempts to compensate for the restricted context.We discuss online and off line on the issues; why we like cyber communication and how we classify the phenomena. The more computer mediated communications we use, the moreissues we have to review beyond words and linguistic principles.